Zakat, Infak, Sedekah, dan Pajak sebagai Sumber Keuangan Negara dalam Perspektif Tafsir Ahkam - Mahabuddin, Muammar; Bisri, Hasan; Athoillah, Muhamad (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
This paper examines the position of zakat, infaq, sadaqah, and taxation as sources of state finance from the perspective of tafsir ahkam. Zakat, infaq, and sadaqah (ZIS) are sharia-based instruments that not only function as acts of individual worship but also possess strategic socio-economic roles in realizing social justice and public welfare. Meanwhile, taxation serves as a state instrument to finance public interests and national development. This study aims to analyze the relevance of Qur’anic verses, particularly Qur’an Surah Al-Baqarah verses 261–262, 267, and 271, as well as Surah At-Tawbah verse 103, in the context of managing state finance based on sharia values. The research employs a qualitative approach through a literature review of the Qur’an, classical and contemporary tafsir works, and relevant fiqh sources. The findings indicate that the Qur’an emphasizes the principles of sincerity, the quality of wealth, and ethical distribution in the implementation of zakat, infaq, and sadaqah. Zakat carries both spiritual and social dimensions that function to purify wealth and the soul, while infaq and sadaqah strengthen social solidarity. In the modern context, the synergy between ZIS and taxation can serve as a foundation for a just, sustainable, and welfare-oriented state financial system.